2016
DOI: 10.1332/204674316x14540714620201
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, child abuse and neglect: patterns of cost and spending

Abstract: This article examines recent data on the costs of poverty, child abuse and neglect (CAN), paying particular attention to contemporary and related patterns of spending in England. The discussion reflects CAN spending associated with some interpretations of Early Intervention. The evidence outlined within this article suggests that the financial costs of poverty and CAN are both substantial and associated. Analyses of spending patterns also suggest E is thinking (Jütte et al., 2014). Evidence on the cost effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…On the one hand, there are underlying demographic and market factors such as population growth, wages and salary agreements, and inflation (Hastings, et al 2015). On the other, there are changes in service demand factors reflecting stressors that result in higher rates of referral to services (Hood, et al 2016;Mason and Bywaters 2016). Poverty, in particular, is a strongly associated characteristic of children who are taken into care (Looked After Children) or have some kind of contact with childrenÕs services (Bramley and Watkins 2008;Bywaters, et al 2014aBywaters, et al , 2017aMason and Bywaters 2016).…”
Section: Provision and Need For Childrenõs Servicesmentioning
confidence: 99%
See 3 more Smart Citations
“…On the one hand, there are underlying demographic and market factors such as population growth, wages and salary agreements, and inflation (Hastings, et al 2015). On the other, there are changes in service demand factors reflecting stressors that result in higher rates of referral to services (Hood, et al 2016;Mason and Bywaters 2016). Poverty, in particular, is a strongly associated characteristic of children who are taken into care (Looked After Children) or have some kind of contact with childrenÕs services (Bramley and Watkins 2008;Bywaters, et al 2014aBywaters, et al , 2017aMason and Bywaters 2016).…”
Section: Provision and Need For Childrenõs Servicesmentioning
confidence: 99%
“…On the other, there are changes in service demand factors reflecting stressors that result in higher rates of referral to services (Hood, et al 2016;Mason and Bywaters 2016). Poverty, in particular, is a strongly associated characteristic of children who are taken into care (Looked After Children) or have some kind of contact with childrenÕs services (Bramley and Watkins 2008;Bywaters, et al 2014aBywaters, et al , 2017aMason and Bywaters 2016). However, there has historically been a greater focus on individualised mediating factors: drug use, maternal mental health, domestic violence, that are often also strongly associated with poverty (Cleaver, et al 2011;Bywaters, et al 2016).…”
Section: Provision and Need For Childrenõs Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…(Krumer-Nevo, 2009, p. 318). Yet, Mason and Bywaters (2016) have observed that poverty and allegations of neglect are so interlinked that prioritising context-blind, policing-type investigations over supportive measures will likely prove both ineffective and financially inefficient. Aotearoa New Zealand child protection history contains instances of counterproductive policy stemming from a context-blind approach.…”
Section: Acknowledging and Addressing Poverty's Impactmentioning
confidence: 99%